Processing of pre-cooked frozen Brussels sprouts: Heat transfer modelling as related to enzyme inactivation and quality stability - Perez Calderon, John Freddy (2019)
The finite element numerical method was applied to simulate heat transfer processes (heating, cooling and freezing) in irregular domains during the production of precooked frozen Brussels sprouts; the effect of temperature on thermo-physical properties in the partial differential equation, and experimental heat transfer coefficients were considered. During precooking, heat transfer was coupled to the inactivation kinetics of thermo-labile and thermo-resistant fractions of peroxidase. The temperature distribution, and enzyme activity in the vegetable domain were modeled; these simulations were validated, obtaining a satisfactory agreement between the predicted values and: i) the experimental time-temperature curves, ii) the residual enzyme activity of peroxidase measured in the vegetable.The simulation of the time-temperature curve during the freezing process is a complex nonlinear problem that requires knowledge of the thermo physical properties changing with temperature. A change of variables based on Enthalpy and Kirchhoff formulations, was adopted for the numerical solution. The effects of precooking times (3,6,10 minutes) on quality parameters of the frozen vegetable (Browing Index, textural properties, residual peroxidase activity, ascorbic acid content) were measured in the samples after freezing and storage during 4 months at -20 °C. The pre-cooking time was optimized to get acceptable quality parameters avoiding peroxidase reactivation during frozen storage.